Rebuilding Hometowns: Religious Worship as an Identity and Tourist Strategies of Place-making - Letizia Carrera; William Calvo-Quirós (Fuori Luogo, 2023)
In a globalized world in which the paths of life project the subjects even in places distant from the birth one and in which the feeling of identity is pluralized and becomes more and more complex, new and stronger mechanisms of resistance and preservation of ties and sense of belonging are generated. The roots tourism represents an answer realized by the emigrants of first, second or even successive generations, able to preserve the link with the territory of origin and, through this, their own identity. This specific form of tourism is therefore, more than any other, a journey into its own history, characterized by the desire to (re)find places connected to its own past or family history. It seems that the identity sought a spatial, physical roots and, in experiencing those places, a sort of confirmation of the fullness of identity.